Wpływ komunikacji marketingowej na zachowania konsumentów w przekroju warstw społecznych w Słowacji - Petrovičová, Janka (The Influence of Marketing Communication on Consumer Behaviour of Social Classes in Slovakia, 2006)
The objective of this article is to present methodology and results of our research in the area of consumer behaviour of social classes is Slovakia. During our desk research we found out that there exist uncovered issues within consumer behaviour. Consumer behaviour have been examined from the point of view of "classical" criteria such age or gender, which were supposed to have influence on consumer behaviour in some way, but we didn't meet with investigating the social class impact on it. We also assumed that there will be some differences between individuals from different social classes in Slovakia. The presented results will join knowledge of two fields - marketing and applied sociology. Our intend was to find out preferences, habits, opinions and attitudes, differences between them within social classes and dependence and its intensity between consumer behaviour within marketing communication and social class.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 267-276